2021
DOI: 10.52547/aassjournal.967
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Autogenous Fascia Relaxation and Spinal Mobility Exercise on Pain and Range of Motion in Elderly Female Patients with Chronic Back Pain

Abstract: Background. This study was to investigate the effects of self-fascial relaxation, stretching, and spinal mobility exercises using foam rollers and elastic bands on elderly women's back pain, pain disability index, and spinal joint mobility. Methods. This study was performed elderly women (65-75years) who had no surgical experience within one year, had more than one clinical result due to back pain, and maintained pain for more than 6 months. The subjects who participated in the study were divided into groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition to physical therapy as standard care procedure, a randomized group of alloHCT patients completed a daily fascia-training program using fascia rolls. In general, fascia training is feasible to improve back flexibilty and to reduce back pain [ 17 20 ]. However, to our knowledge, this is the first study investigating the feasibility and its potential effects of special fascia training in patients undergoing alloHCT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to physical therapy as standard care procedure, a randomized group of alloHCT patients completed a daily fascia-training program using fascia rolls. In general, fascia training is feasible to improve back flexibilty and to reduce back pain [ 17 20 ]. However, to our knowledge, this is the first study investigating the feasibility and its potential effects of special fascia training in patients undergoing alloHCT.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle atrophy caused by medication and prolonged inactivity frequently leads to back pain in patients after alloHCT. Previously published studies could verify positive effects of fascia training on back pain in healthy adults [ 17 , 18 ]. In comparison, the IG of the present study reported a tendency towards a reduction in back pain from pre to post fascia-training intervention, whereas the CG showed a slight increase in back pain at t3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation